The trifecta of adulthood: Housing, partnering and childbearing trajectories - Tan, Jolene (Advances in life course research, 2023)
Substantial changes in residential transitions and family formation patterns have been observed in Western societies, but less attention has been paid to the de-standardisation of adulthood pathways in East Asian contexts, where unique social, economic and cultural circumstances may produce diverse trajectories that are less explored in existing theoretical and empirical frameworks. Adopting a life course perspective, this study identifies the multi-trajectories of housing, partnering and childbearing across adulthood in Taiwan, a setting marked by high housing costs and low fertility rates. Data from the Taiwanese Panel Study of Family Dynamics 2000-2020 (N = 6,931) were used for group-based trajectory modelling, and mixed-effects multinomial regression was employed to examine the likelihood of group membership given early-life resources and social origin. Six common housing-partnering-childbearing trajectories were identified. The most prevalent living arrangement was living in parental homes (50.7%), followed by rental homes (25%), self-owned homes (15.5%) and dorms or other (8.8%). Union formation generally precedes childbearing, whereas housing transitions may occur at various time points. Young adults' home-leaving and homeownership access appear to be closely related to their parental backgrounds, such as their parents' educational attainment and occupational status. Overall, the findings are consistent with the de-standardisation of pathways to adulthood, demonstrating the diversity in adult trajectories and the lack of a single dominant pattern.